A Project Report on Hue Preserving Color Image Enhancement Using Multiscale Morphology - ABDUL RAZAK, CHETHAN R and JAYA PRAKASH S R (2013)
INTERNAL GUIDE : Praveena K EXTERNAL GUIDE : Prayoona Valsalan and Naveen Kumar G N USN NO : 1MJ09EC001, 1MJ9EC013, 1MJ09EC020 CARRIED OUT AT : MVJ College Of Engineering Bangalore-560067 ACC NO : PR1970
Keywords: Hue Preserving Color Image Enhancement Using Multiscale Morphology